Marked up-regulation of anti inflammatory cytokine gene expression in the peripheral blood mononuclear cells of postpartum cows with endometritis - ISLAM, RAFIQUL; KUMAR, HARENDRA; NANDI, SUKDEB; PATRA, M K (The Indian Journal of Animal Sciences, 2021)
This study was designed to determine the mRNA expression profile of inflammatory and anti-inflammatory cytokines in peripheral blood mononuclear cells (PBMC) of endometritic and non-endometritic cows to find out a possible marker for diagnosis of endometritis. Cows (21) including 12 endometritic, and 9 normal (non-endometritic) that did not develop uterine diseases postpartum (pp) were selected. Expression profile (mRNA) of cytokines, viz. IL-1β, TNFα, IL-8 and IL-4 in endometritic cows relative to non-endometritic was studied in PBMC isolated from the blood of the cows collected within 4 to 5 weeks pp. Fold difference (n-fold) in cytokine gene expression in the PBMC of endometritic cows relative to normal was calculated using relative quantification method (2-ΔΔCt). The relative fold change in gene expression for IL-1 was significantly lower in endometritic animals (0.31) than in cows that did not develop endometritis. Significant up-regulation was noted for the proinflammatory cytokine TNFα (9.53 fold and anti-inflammatory cytokine IL-4 (90.09) in cows suffering from endometritis relative to nonendometritic cows. Up-regulation of chemokine IL-8 gene (6.25 fold; was also observed in endometritic compared to non-endometritic cows. Highest and significant up-regulation of mRNA expression for IL-4 followed by TNFα in PBMC of endometritic cows recorded in the study may indicate the development of endometritis in postpartum cows.